Marriage and the duties of the marriage relations : in a series of six lectures addressed to youth and the young in married life / by George W. Quinby. - Quinby, G. W. (George Washington), 1810-1884. (Tufts University. Tisch Library., 2015)
1 online resource (216 pages).